Miso without kōji: nesashi miso ecology driven by spontaneous fermentation with Mucor plumbeus - Kothe, Caroline Isabel; Mak, Tiffany; Julienne, Achille; Okazaki, Kiyo; Jahn, Leonie J.; Evans, Joshua D. (Frontiers in Microbiology, 2026)
Nesashi miso is a rare, traditionally fermented soybean paste from Japan, and unlike most misos is produced through spontaneous fermentation without the use of a kōji starter. Here we analyzed a nesashi miso alongside two other misos from the same producer (rice and black soybean) as well as a hatchō miso from another producer which, like the nesashi, is based only on soybeans. Shotgun metagenomics confirmed that while Aspergillus oryzae dominated the three kōji-based misos, nesashi miso lacked this starter culture, and revealed that it was instead dominated by other filamentous fungi, mainly Mucor spp. and Penicillium spp., and contained typical yeast and bacterial genera found in traditional misos such as Zygosaccharomyces and Tetragenococcus. Principal component analysis (PCA) of 65 publicly available metagenomes showed that the nesashi miso sample clustered with other spontaneous solid-state fermentations like Chinese qu rather than with traditional kōji-based misos. To further characterize this unique fermentation, we isolated the Mucor sp. from nesashi miso, and sequenced it using long-read genomic sequencing. Pangenomic analysis confirmed its identity as M. plumbeus, and revealed close relationships between food- and environment-derived strains, suggesting that some Mucor species may already be naturally equipped to grow, establish and function in food fermentation niches. The nesashi strain specifically shared a large core genome with M. racemosus C, a strain patented for use in food, suggesting the former’s potential for use in and potentially even adaptation to food environments. Functional annotation highlighted unique genes in the food strain group associated with amino acid metabolism, which may contribute to flavor formation. Together, these findings bridge traditional fermentation practices with meta/genomic insights, highlighting the built fermentation environment as a reservoir of potential starter cultures and the genus Mucor as a worthy candidate for future food fermentation research and innovation.